Tuberous sclerosis associated with autosomal dominant polycystic kidney disease: Case report about of the TSC2/PKD1 contiguous gene syndrome - Queiroz, Rodolfo M.; Gomes, Michela P.; Valentin, Marcus V. N.; Miyake, Cecília H.; Abud, Lucas G.; Silva, Marcio de Castro e (Medicina (Ribeirao Preto), 2016)
We present a case of a young woman with chronic kidney disease, with a history of seizures, episodes of spontaneous pneumothorax and left nephrectomy. The retrospective study of the image exams showed liver, kidney and lung cysts; in addition to cortical tubers and subependymal nodules in the brain. The pathologic evaluation of kidney surgically removed characterised adult renal polycystic disease. The clinical review also with these tests revealed the diagnosis of tuberous sclerosis, and autosomal dominant polycystic kidney disease, suggesting contiguous gene syndrome TSC2/PKD1